2015
DOI: 10.1128/aac.02009-15
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Available Medicines Demonstrating Anti-Toxoplasma Activity

Abstract: e Toxoplasma gondii is an apicomplexan parasite of humans and other mammals, including livestock and companion animals. While chemotherapeutic regimens, including pyrimethamine and sulfadiazine regimens, ameliorate acute or recrudescent disease such as toxoplasmic encephalitis or ocular toxoplasmosis, these drugs are often toxic to the host. Moreover, no approved options are available to treat infected women who are pregnant. Lastly, no drug regimen has shown the ability to eradicate the chronic stage of infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
67
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 103 publications
2
67
0
1
Order By: Relevance
“…The search for new anti-Toxoplasma gondii drugs has been active for several decades [12,13], but only a few drugs are currently approved for use in humans [1,27]. Although sulfa drugs can be effectively used for the prevention and control of T. gondii infection in humans and animals, their side effects should not be ignored [28].…”
Section: Discussionmentioning
confidence: 99%
“…The search for new anti-Toxoplasma gondii drugs has been active for several decades [12,13], but only a few drugs are currently approved for use in humans [1,27]. Although sulfa drugs can be effectively used for the prevention and control of T. gondii infection in humans and animals, their side effects should not be ignored [28].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, there is a compelling need for safe and effective treatments for toxoplasmosis (7,8). A comprehensive analysis of the present stage of toxoplasmosis treatments has recently been published (5,9).…”
mentioning
confidence: 99%
“…Fluoroquinolones are the known DNA replication inhibitors that target prokaryotic type II topoisomerases (Collin et al, 2011). In two studies, researchers showed that derivatives of the antibiotic ciprofloxacin, a fluoroquinolone, are active against T. gondii tachyzoites both in vitro and in vivo (Neville et al, 2015). While all mice treated with ciprofloxacin died by day 10 post-infection, some mice treated with ciprofloxacin derivatives remained alive for at least 60 days, suggesting that ciprofloxacin derivatives cured T. gondii infection in treated mice (Dubar et al, 2011; Martins-Duarte et al, 2015).…”
Section: Discussionmentioning
confidence: 99%